ANARKI ARSITEKTUR - Maria Adriani (Fakultas Ilmu Budaya universitas Hasanuddin, 2018)
This paper is offering possibilities for architecture to leave from the systems that bind it byuncovering these systems that work on architecture. In general understanding, arhitecture is seen as an “exclusive” science and practices yet in fact it closely related to the social world, and therefore susceptible to be a repressive tool. By focusing on architectural practices in Indonesia, this discussion is placed in the sphere of spatial production, scientific power and idea production. In the contexts where architecture has bee in the comfort zone without criticsm for almost 30 years, this paper opens the structured-arrogance of architecture which ties into the question of to what objective goals of architectural practices are dedicated.